Differentiating border-zone tissue from post-infarct scar using ripple mapping during VT ablation. (19th May 2022) - Khanra, D; Calvert, P; Wright, P; Hughes, S; Mahida, S; Hall, M; Todd, D; Gupta, D; Luther, V
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Areas of post-infarct ventricular scar and border-zone slow conduction are often highlighted on a bipolar voltage map with generalized values 0.5mV–1.5mV. The true voltage that differentiates regions of conducting from non-conducting tissue is unknown. Ripple Mapping (RM)displays allows conducting tissue to be seen as areas supporting Ripple activation, and non-conducting tissue as areas devoid of Ripple activation. Purpose: We describe application of Ripple Maps to differentiate areas of scar from conducting tissue during ischemic VT ablation. Methods: Dense bipolar voltage maps were created (Pentaray catheter, pacing 80-100bpm) and presented as a single value (e.g. 0.5mV-0.5mV) to binarize the color display (red and purple). RMs were superimposed on the voltage map and played above a pre-set noise threshold (>0.05mV). The voltage map mV limit was sequentially reduced ("border-zone threshold") until only those areas devoid of Ripple bars appeared red. The surrounding border-zone supporting ripple activation thus appeared purple. We performed off-line analysis of border-zone voltage thresholds from a series of RM guided VT ablations. Results: 10 consecutive patients (LVEF 32.3±7.5%) with remote myocardial infarction underwent VT ablation (median 19days (IQR 8-33) since last VT). Bipolar voltage mapping (5873±2841 points, median shell area 224cm2), revealed voltages<0.5mV covered a median 11% (IQR 7-17%) of the shell. The border-zone voltage threshold was median 0.2mV (range 0.12mV - 0.3mV). Non-conducting tissue below this value covered only median 5% (IQR 3-7%) of the entire shell. VT was mappable in 4 patients, and the isthmus was bordered by tissue below the same border-zone threshold as found in normal rhythm. The border-zone was homogenized with ablation(40-50W, median 29 mins (IQR 22-33), and clinical VT was non-inducible in all, and 9 pts (91%) remain sustained VT-free at median 90-day follow-up (IQR 23-139), 2-weeks blanking period). Picture 1 presents an infero-lateral LV infarct collected in an RV paced rhythm (7340points) and displayed at conventional bipolar voltage settings 0.5-1.5mV. Tissue with voltages<0.5mV appear red and cover 30% of the total area. In this case, this border-zone voltage threshold was defined as 0.25mV. Non-conducting tissue, seen as areas devoid of ripple bars below this value, now appeared as red, and covered only 11% of the total area. Picture 2 demonstrates the morphologies of 4 poorly tolerated induced VTs during this case. Each had near perfect pacemaps to the exit sites of border-zone tissue defined using this approach, and were targets for ablation resulting in complete non-inducibility and no VT recurrence in early follow-up. Conclusion: The bipolar voltage that differentiates putative scar from bordering conducting tissue is unique to each patient, and far lower than 0.5mV-1.5mV. RM presents a practical approach to visualize the border-zone activation to guide ablation.